An audit of general practitioner involvement in public community mental health care. (October 2015) - Jang, Jae; Futeran, Shuli; Large, Matthew; Curtis, Jackie
Objective: Existing guidelines suggest that collaboration between general practitioners and mental health services may improve the physical health of people with serious mental illness. This study investigated the extent of general practitioner involvement in a community mental health centre and examined whether the presence of a documented general practitioner in the patient's medical records was associated with markers of better health outcomes. Methods: The medical records of current patients were audited, including those receiving medical care and case management and those only receiving medical care. The demographic and diagnostic information, evidence of metabolic screening, blood test results, and medications of patients with a recorded general practitioner were compared with those of patients with no recorded general practitioner. Results: Ninety-eight of 191 (51%) of patients had details of a general practitioner documented in their medical records. There were no significant differences in rates of metabolic screening between the two groups. Those with a general practitioner had more medical diagnoses and were taking a greater number of psychiatric medications. Conclusion: Although the medical comorbidities of serious mental illness are becoming increasingly recognised, our findings suggest the need for ongoing and coordinated efforts by policymakers, general practitioners, mental health services and patients to ensure the health and longevity of people with serious mental illness.